(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The pandemic and the ethical dilemma of limited resources: who to treat? The article assesses the issue of the allocation of health care resources in conditions of scarcity in the context of the bioethical discussion in relation to the CoViD-19 pandemic and the question of access to treatment. The following are analyzed: libertarian theory, utilitarian theory and theories that focus on equality between human beings, comparing conceptual premises and arguments critically, and analyzing the main documents of national and international scientific societies and bioethics committees.